Pengaruh Pemberian Ekstrak Sambiloto (Andrograpis paniculata Ness) Terhadap Produktivitas Pertumbuhan Ayam Broiler (Gallus domesticus): The Effect of Sambiloto Extract (Andrograpis Paniculata Ness) on the Growth Productivity of Broiler Chickens (Gallus Domesticus) - Mardhianto, Mardhianto; Mudawaroch, Roisu Eny; Rinawidiastuti, Rinawidiastuti (Jurnal Riset Agribisnis dan Peternakan, 2022)
This research aims to determine the effect of giving bitter extract on the productivity of broiler chickens. The method used in this research was a completely randomized design (CRD) with 5 treatments using bitter extract at different doses, namely treatment (0; 4; 8; 12; 16 ml/kgBB) and 5 replications. The parameters observed were feed consumption, drinking water consumption, daily weight gain, feed conversion and feed efficiency. The data obtained were analyzed using the Analysis of Variance (ANOVA) test. If there were differences, the Duncan New Range Test (DMRT) was carried out. The research results showed that giving bitter extract had no significant effect (P>0.05) on feed consumption, drinking water consumption, daily weight gain, feed conversion and feed efficiency. Feed consumption has no significant effect at 154.02; 164.94; 156.80; 152.36; 163.00 g. Drinking water consumption has no significant effect at 222.3; 224.3; 227.3; 227.1; 227.1 ml. daily weight gain has no significant effect at 72.48; 71.78; 74.22; 74.22; 76.58 g. Feed conversion has no significant effect at 2.08; 2.24; 2.06; 2.02; 2.08. Feed efficiency has no significant effect at 42; 40; 42; 42; 42 %. The conclusion shows that all research parameters have no real effect because the addition of bitter extract cannot increase the productivity of broiler chickens.